ВЛИЯНИЕ ГРАВИТАЦИОННОГО ЛИНЗИРОВАНИЯ НА ФУНКЦИЮ СВЕТИМОСТИ КВАЗАРОВ - Бухмастова, Ю. Л. (Одеські астрономічні публікації, 2011)
The function of quasar distribution on apparent brightness is discussed. This function is found on base of suggestion that quasars, at least partly, are strong gravitational lensing images of the active nuclei of distant galaxies. This function is obtained using the Schechter luminosity function of sources, luminosity function of sources in form two- power law and also the magnification probability law for various models of gravitational lenses. At finding of theoretical function of the quasar distribution on apparent brightness the theorem on probability density of multiplication of random quantities. It is shown that slopping of this function in the event of weak quasars varies from -1 before -2, as for usual galaxies. In the case of bright quasars a slopping to functions of distribution on apparent brightness is defined basically by lensing effect and is limited from below the value -3. Good agreement of theory and observations allows to expect that quasar are gravitational lensing images of the active nuclei of distant galaxies statistically. If basic suggection is true the luminosity functions of galaxies and apparent brightness of quasars are not independent, but connected by means of differential probability of lensing.